ANALISIS KEBUTUHAN PENGEMBANGAN BAHAN AJAR IPAS BERBASIS ETNOFOTOGRAFI UNTUK MENINGKATKAN LITERASI BUDAYA - Saiful Rohman (STKIP Subang, 2023)
Literature and media have a significant influence in disseminating information about certain cultures, but without cultural understanding and literacy, information will just be information. The aim of the research is to analyze the need for developing ICT teaching materials to increase cultural literacy. The research method used is desk research using a qualitative approach. Data collection techniques using library research. The results of the research are in the form of recommendations for steps in selecting teaching materials, including: (1) formulating specific objectives, (2) determining the target areas to be achieved: cognitive, affective and psychomotor, (3) choosing strategies that are appropriate to the learning area being studied. has been determined, and (4) selecting the appropriate media.